Community/public health nursing practice health for families and populations - Maurer, Frances A.; Smith, Claudia M. (Elsevier/Saunders, 2013)
Focusing on practical, need-to-know information, Community/Public Health Nursing Practice helps you learn how to apply the nursing process at the community and family level. It features an engaging, easy-to-understand writing style, as well as assessment tools, detailed case studies, adn clinical examples that demonstrate how key concepts apply to real-world practice. Additional resources on the companion Evolve website expand and enhance content within the text.